2013
DOI: 10.1186/1472-6890-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Pepsinogen I and II expressions in situ and their correlations with serum pesignogen levels in gastric cancer and its precancerous disease

Abstract: BackgroundSerum pepsinogen (PG) I/II ratio has been widely used as “serological biopsy” for the screening of gastric cancer (GC) and atrophic gastritis (GA). However, study concerning in situ expression of PGs is currently insufficient, particularly for their relationship with serum PGs levels. This study was designed to investigate in situ expression of PGI and PGII in subjects with normal mucosa (NOR), superficial gastritis (GS), GA and GC, and to evaluate the correlations between PGs expressions in situ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Besides the host genetics, histological PGC expression could also be affected by several other factors such as status of gastric mucosa, location of affected or selected tissues, and state of H. pylori infection. Especially, the status of gastric mucosa and the location of tissue have significant effects on in situ PGC expression levels as described in previous studies [16] , [17] . Therefore, detection of histological PGC protein in cancerous tissues could not be accomplished in experimental practice.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Besides the host genetics, histological PGC expression could also be affected by several other factors such as status of gastric mucosa, location of affected or selected tissues, and state of H. pylori infection. Especially, the status of gastric mucosa and the location of tissue have significant effects on in situ PGC expression levels as described in previous studies [16] , [17] . Therefore, detection of histological PGC protein in cancerous tissues could not be accomplished in experimental practice.…”
Section: Discussionmentioning
confidence: 60%
“…Streptavidin-peroxidase two-step immunostaining was then performed according to kit instructions (Kit-9801D2, Maixin Company, Fujian, China). A more detailed method for detecting PGC protein in situ has been described previously [17] .…”
Section: Methodsmentioning
confidence: 99%
“…Increased circulating pepsinogen levels and increased leakage of plasma protein into the gastric lumen are typical of parasitised animals [ 49 , 50 ] and are probably caused more by inflammation than by worm chemicals. Hyperpepsinogenaemia is considered to be evidence of a leaky abomasal mucosa in many forms of gastritis and is used as a marker for human Helicobacter pylori infection [ 47 , 48 ]. Eosinophils accumulated at the base of the gastric glands ( Fig 4 ) where the chief cells are located, supporting a role for greater permeability in the gland region where pepsinogen is secreted.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mucosal permeability is a major contributor to hyperpepsinogenaemia associated with parasitism, as well as other forms of gastritis [ 47 , 48 ], and leakage of plasma protein and pepsinogen into the gastric lumen [ 49 , 50 ]. The relative importance of direct effects of ES products, physical contact with parasites and inflammation have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Zoalfaghari A et al have proved that the PGI and PGI/II ratio are significantly decreased in AG patients compared with the controls, and these two factors are potential biomarkers for screening AG with high sensitivity and specificity [14]. Ping L et al have indicated that the serum PGI, PGII, and PGI/II ratio are closely related to the occurrence of GC and its precancerous disease [15]. Zhang XM et al have confirmed that patients with early and advanced GC have a significantly lower PGI/II ratio than patients with AG [16].…”
mentioning
confidence: 99%